EFFECT OF REGIONAL OWN REVENUE, GENERAL ALLOCATION OF FUND AND SPECIAL ALLOCATION OF FUND FOR CAPITAL EXPENDITURE BUDGET ALLOCATION - Saifudin Saifudin; Septiana Sari (Universitas Muhammadiyah Metro, 2016)
The purpose of first regional autonomy for increase service public and economy every regional. The purpose of research for is to determine whether there is the of the Region Own Revenue, General Allocation Fund and Special Allocation of Fund for Capital Expenditure Budget Allocation. The Population of research this is all government District and City in Central Java of twenty nine District and Six City. The research used secondary data of Actual Income and Expenditure budget realization report of Government province Central Java the years of 2010-2013. The way to analyze the data by using multiple linier regression analysis. Based on the result of this research concluded that partially Regional Own Revenue and General Allocation Fund has of the effect on Budget Capital Expenditure. While the Special Allocation Fund does not effect on Budget Capital Expenditure. Simultaneously, The Regional Own Revenue, General Allocation Fund and Special Allocation Fund effect on Budget Capital Expenditure. Keywords : Regional Own Revenue, General Allocation Fund, Special Allocation Fund, Capital Expenditure, and Regional Autonomy.